2023
DOI: 10.1186/s13005-023-00381-2
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic and its possible impact on the treatment of odontogenic and intraoral abscesses

Florian D. Grill,
Paulina Rothlauf,
Lucas M. Ritschl
et al.

Abstract: Most odontogenic and intraoral abscesses can be treated on an outpatient basis with local anesthesia. However, severe disease progression may require an incision under general anesthesia (GA) with postoperative inpatient treatment. This study aimed to evaluate the first “COVID-19 year” in Germany and compare the first “COVID-19 year” with the two previous years. All consecutive cases with odontogenic or intraoral abscesses treated in an outpatient or inpatient setting between 2018 and 2021 were included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Marchant et al [22] found that while the severity of maxillofacial fractures decreased postpandemic and the overall incidence remained the same, Hispanic and firearm-caused maxillofacial fractures increased. This decrease in the severity of trauma has been validated in multiple studies [23][24][25][26][27][28][29][30][31][32], with differences found in published studies on the increase or decrease in emergency department attendance by age group [33][34][35][36]. A possible effect during the most severe moments of the pandemic was the lower willingness to seek medical attention in subacute maxillofacial processes (such as precancerous lesions, cancer, or infections) and the prognostic implication that this implied [30,37].…”
Section: Discussionmentioning
confidence: 83%
“…Marchant et al [22] found that while the severity of maxillofacial fractures decreased postpandemic and the overall incidence remained the same, Hispanic and firearm-caused maxillofacial fractures increased. This decrease in the severity of trauma has been validated in multiple studies [23][24][25][26][27][28][29][30][31][32], with differences found in published studies on the increase or decrease in emergency department attendance by age group [33][34][35][36]. A possible effect during the most severe moments of the pandemic was the lower willingness to seek medical attention in subacute maxillofacial processes (such as precancerous lesions, cancer, or infections) and the prognostic implication that this implied [30,37].…”
Section: Discussionmentioning
confidence: 83%